Screening of Acetamiprid Tolerant Plant Growth Promoting Microorganism - Tejaswini, GSNR; Devi, S. Shalini (International Journal of Scientific Research in Biological Sciences, 2019)
Increased demands for food have also increased the usage of pesticides. A pesticide not only kills the pests and pathogens but it also kills microorganisms that are beneficial to plant. So plant growth promoting microorganisms that are tolerant to pesticides would help to enrich soil microorganisms thus protecting the environment. In the present work four soil samples were collected from agricultural fields where pesticide usage was a regular practice. Acetamiprid tolerant microbes were isolated by using acetamiprid amended minimal agar medium. Streptomyces AT (acetamiprid tolerant) isolate was isolated and its PGPR properties were evaluated. The isolate was found to posses properties like IAA secretion, phosphate solubilisation and siderophore production. Coriandrum sativum (coriander) was used as a model plant for evaluation of plant growth promoting properties of promising isolate, Streptomyces AT. The coriander seedlings were grown in soil inoculated with the AT1 isolate, Control plants were maintained by growing in un-inoculated soil. Root length, shoot length and number of plants were measured after 10 days of sowing. Out of 60 coriander seeds sown in each pot, 25 and 50 seeds got germinated in uninoculated and inoculated soils respectively. The average root length of plants grown in uninoculated and inoculated soils was recorded as 37mm and 59mm respectively. The average shoot length of plants grown in uninoculated and inoculated soils was recorded as 34mm and 64mm respectively.